Non-pharmacological therapies of traditional Chinese medicine in prediabetes: a systematic review and network meta-analysis of randomized controlled trials - Ximing Qi; Tianzuo Wang; Lin Liao (Frontiers in Endocrinology, 2026)
Background Prediabetes is an independent risk factor for diabetes complications and all-cause mortality. Non-pharmacological therapies of traditional Chinese medicine (NPTTCM) offer promising alternatives for prediabetes, yet their comparative efficacy remains unclear. Objective The present study aimed to evaluate the efficacies of 6 NPTTCM (acupuncture, acupoint catgut embedding (ACE), Baduanjin, electroacupuncture, massage and Taiji) in prediabetes intervention. Methods Eight databases were searched for randomized controlled trials (RCTs). The network meta-analyses were performed to estimate mean differences and 95% confidence intervals and surface under the cumulative ranking curve (SUCRA) was used to rank NPTTCM. Results Fifty-one RCTs (4,129 participants) were included. Massage, electroacupuncture, Baduanjin and acupuncture significantly reduced fasting plasma glucose (FPG) compared with lifestyle interventions. Massage (SUCRA: 99.3%) was the most effective in FPG reduction, followed by electroacupuncture, Baduanjin, acupuncture. All therapies significantly improved 2-hour postprandial plasma glucose (2hPG), among them, massage (SUCRA: 94.1%) was the best, followed by electroacupuncture, Taiji, acupuncture, Baduanjin and ACE. Acupuncture (SUCRA: 81.8%) was the only intervention that significantly reduced HbA1c. Furthermore, electroacupuncture, massage and acupuncture significantly reduced body mass index (BMI), with electroacupuncture (SUCRA: 98.8%) the best, followed by massage and acupuncture. Electroacupuncture and Baduanjin significantly reduced total cholesterol, with electroacupuncture (SUCRA: 79.7%) the best, Baduanjin the second. ACE and Baduanjin significantly reduced triglycerides, with ACE (SUCRA: 74.9%) the best, Baduanjin the second. Conclusion NPTTCM may provide potential benefits for improving metabolic outcomes in prediabetes. Massage showed a favorable ranking for reducing FPG and 2hPG, while acupuncture showed a favorable ranking for HbA1c reduction. Electroacupuncture and ACE showed potential benefits for BMI and lipid management. However, given the limitations, these results should be interpreted with caution. Future head-to-head and rigorously designed studies are needed to provide further evidence. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=1129592 , identifier CRD420251129592.